Type 2 diabetes mellitus status in obese patients following sleeve gastrectomy or one anastomosis gastric bypass - Gavriella Zoi Vrakopoulou (Nature Portfolio, 2021)
Abstract This study aims to compare sleeve gastrectomy (SG) and one anastomosis gastric bypass (OAGB) in terms of remission of type 2 diabetes mellitus (T2DM) in obese patients. All T2DM patients were followed-up for at least 36 months. The primary outcome was remission of T2DM. Secondary endpoints included weight reduction and the procedure’s impact on quality of life. In total, 53/1177 morbidly obese patients who underwent SG (Group A, n = 28) or OAGB (Group B, n = 25) had T2DM. Preoperatively, the mean Body Mass Index (BMI) values were 52.2 ± 8.5 kg/m2 and 52.9 ± 10.9 kg/m2 for Group A and Group B, respectively. Six patients in Group A were insulin dependent, while 8 were insulin dependent in Group B. After 36 months, diabetes remission was achieved by only 10 patients (35.7%) in Group A. However, in Group B, 22 patients (88%) remained off antidiabetic agents (p < 0.0001), with ΔHbA1c (%) reaching 1.4 ± 1.5% in Group A and 2.7 ± 2.1% in Group B (p = 0.02). Excess weight loss% (%EWL) was again significantly different between the two groups (MA = 79.8 ± 14.5%, MB = 93.3 ± 16.0%, p = 0.003). OAGB is more effective in improving glycaemic control and %EWL, with almost immediate resolution of diabetes, as well as long-term weight loss.